Global English, Global Technology, Global Learning (Research Journal on Multi-disciplinary Issues, 2026)
The examine several ways to look at Global English, Global Technology, Global Learning, including UNESCOs report "Reimagining Our Futures Together", (International Commission on the Futures of Education, 2021) which sought to address urgent global challenges by discussing major roles for global perspectives in education. What is the meaning of global citizenship education (GCED), within UNESCOs proposed non-neutral transformative We question it as truly neutral, when presented together with one of three possible frameworks? However, GCED represents value. In that regard, Nepal’s education should consider global URL: www.nepjol.info citizenship, within the discussion around the 2030 Agenda for promoting solidarity, justice and equality at all education institutions. However, in seeking answers, we also examine disruptive proposals guided by four research questions offering other alternatives around economic and socially inclusive environmental development in line with peace and security-an essential pillar of the SDGs. We critique universities as institutions that take a true constructivist epistemology (but don’t) with comprehensive conceptions of education, making explicit recognition of diversity and recognizing the active role of individuals and groups. For a practical perspective, we move away from the Western-centrism and the UN nonneutral approach, and include alternatives, such as Critical Incident Analysis (CIA) for teaching practitioners in many and varied situations as a means of understanding their own teaching practice and thereby becoming better teachers. This paper does not provide answers, only room for further discussion on the different perceptions of what Global Education System between the Global North and the Global South should look like.